Pengembangan Simulasi berbasis Augmented Reality: Penyambungan Kabel Fiber dan Jaringan FTTH - Pujayani, Ni Made Dwi; Sindu, I Gede Partha; Saskara, Gede Arna Jude (Jurnal Profesi Insinyur Universitas Lampung, 2025)
Abstract. This study aims to develop Augmented Reality (AR)-based learning media on fiber optic cable and FTTH network materials to support FTTx learning. The method used is Research and Development (R&D) with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. The developed media was tested through blackbox testing, whitebox testing, individual testing, small group testing, field testing, as well as pretest and posttest to measure its effectiveness. The test results showed that the application functioned well and was considered very feasible, as indicated by a small group test percentage of 91.5% and a field test percentage of 91.47%. The responses of students and teachers also showed very positive assessments. Overall, this AR learning media was declared valid, effective, and practical for use in fiber optic and FTTH network learning.